Vemurafenib resistant melanoma cells acquire mesenchymal stem cell-like properties - A. A. Vartanian; O. S. Burova; Kh. S. Vishnyakova; I. V. Samoylenko; V. A. Misyurin; E. E. Egorov; O. O. Ryabaya; M. A. Baryshnikova (Успехи молекулярной онкологии)
Background. Activating mutations in the BRAF gene leads to a constitutive activation of the MAPK signaling. The highly selective BRAFV600E inhibitor, vemurafenib, improves the overall survival of BRAF-mutant melanoma patients. However, despite the excellent results of response rate, the average duration of the response was short and acquired resistance develops in most BRAF mutated melanoma patients within a few months. Objective: to derive melanoma cell lines from surgical species of patients with BRAF mutant melanomas resistant to vemurafenib and to elucidate the mechanisms involved in acquired drug resistance.Materials and methods. Mel Ki and Mel F1702 melanoma cells were obtained from metastases of disseminated melanoma patients with BRAFV600E mutation. 2D tumor cell culture, MTT test, immunicytochemistry, flow cytometry, real-time polimerase chain reaction and osteogenic and adipocytic differentiation were used in the study.Results. We have derived two melanoma cell lines Mel Ki and Mel F1702 from tumor samples of patients with BRAFV600E mutation resistant to vemurafenib. These cells were homogenous and had fibroblastic morphology. The IC50 values for Mel Ki and Mel F1702 were 4.7 and 6.3 μM, respectively. The expression of cancer-testis antigens was not detected in both types of cells suggesting the stemness of Mel Ki and Mel F1702 melanoma cells. The immunophenotypic profile of the vemurafenib resistsant melanoma cells showed the expression of typical mesenchymal stem cells markers such as CD90, CD105 and CD44. In addition, we found that the melanoma cell lines derived from tumor resistant to vemurafenib differentiated into osteoblastand adipocyte-like cells. Conclusion. In this study we are offering an experimental evidence of the phenotypic transition of the vemurafenib-resistant melanoma cells into mesenchymal stem-like cells.